Measuring the Hedonic and Utilitarian Dimensions of Consumer Attitude - Voss, Kevin E.; Spangenberg, Eric R.; Grohmann, Bianca (Journal of Marketing Research, 2003)
This article reports the development and validation of a parsimonious, generalizable scale that measures the hedonic and utilitarian dimensions of consumer attitudes toward product categories and different brands within categories. The hedonic/utilitarian (HED/UT) scale includes ten semantic differential response items, five of which refer to the hedonic dimension and five of which refer to the utilitarian dimension of consumer attitudes. The authors conducted six studies to establish the unidimensionality, reliability, and validity of the two HED/UT subscales. In reaching the final scale, the authors also develop and implement a unique process of paring down a psychometrically sound but otherwise too large set of items. Nomological validity is established by replacing a typical, one-dimensional attitude toward the brand measure with the hedonic and utilitarian dimensions in a central route processing model. Results suggest that the hedonic and utilitarian constructs are two distinct dimensions of brand attitude and are reliably and validly measured by the HED/UT scale.